Massive Open Online Courses: a bibliometric review - Sobral, Sónia Rolland (2020)
Massive Open Online Courses (MOOCs) are open courses offered to an indefinite number of participants and accessible through virtual learning environments. These courses have been the subject of research all over the world. The purpose of this paper is to analyze the scientific production on Massive Open Online Courses in journals indexed in Clarivate Analytics’ Web of Science and Elsevier’s Scopus. The sample is composed by 1908 articles in total. The results obtained by bibliometric analysis showed that the publication continue to increase, in which journals they are published, which are the organizations and countries that publish the most, and which are the most cited articles. We concluded that since Massive Open Online Courses are a reality, there still seems to be a possibility for evolution in good quality publications.